2016
DOI: 10.1186/s13018-016-0364-3
|View full text |Cite
|
Sign up to set email alerts
|

Two-stage total hip arthroplasty for patients with advanced active tuberculosis of the hip

Abstract: BackgroundTreatment of advanced active tuberculosis (TB) of the hip is confronted with great challenges. Although one-stage total hip arthroplasty (THA) is considered as a safe procedure for most patients by some authors, there are still exceptions. The purpose of this paper was to investigate the feasibility and effectiveness of two-stage THA for selected patients with advanced active TB of the hip.MethodsNine consecutive patients with advanced active tuberculous arthritis of the hip were reviewed in this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
2
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 21 publications
2
37
2
4
Order By: Relevance
“…El compromiso de la cadera es el segundo más frecuente después de la columna, 2 y su tratamiento presenta controversias en relación a su manejo médico y quirúrgico. 5 El caso presentado muestra un paciente con una tuberculosis activa de la cadera que determinó una destrucción articular avanzada. Se describe entonces como se realizó su manejo médico y posterior ATC en 2 tiempos como una alternativa de tratamiento efectiva para ese complejo escenario.…”
Section: Discussionunclassified
See 3 more Smart Citations
“…El compromiso de la cadera es el segundo más frecuente después de la columna, 2 y su tratamiento presenta controversias en relación a su manejo médico y quirúrgico. 5 El caso presentado muestra un paciente con una tuberculosis activa de la cadera que determinó una destrucción articular avanzada. Se describe entonces como se realizó su manejo médico y posterior ATC en 2 tiempos como una alternativa de tratamiento efectiva para ese complejo escenario.…”
Section: Discussionunclassified
“…10 Algunos autores recomiendan un largo periodo de quiescencia antes de la cirugía, siendo utilizados intervalos desde ATC inmediata hasta 20 años posterior al inicio de la enfermedad. 5,10,11 En pacientes con infección activa, el tratamiento quirúrgico con una ATC de forma primaria en un tiempo es controversial por el riesgo potencial de reactivación de la enfermedad. No obstante, la reactivación de la TBC ocurre en pacientes en que no se diagnosticó la etiología inicialmente, en aquellos sin tratamiento preoperatorio o que no presentaron una adherencia adecuada.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Subsequent report has found that the use of antibiotic-loaded spacers in two-stage THA may be considered as a suitable method for the treatment of primary SA in adults [8]. In addition, Li et al [9] have reported that twostage THA using debridement or femoral head resection with antibiotic-loaded spacer implantation is effective in the treatment of advanced active tuberculosis of the hip and have demonstrated that the outcomes of two procedures are consistent. Therefore, it is necessary for us to further demonstrate the treatment of between debridement and antibiotic-loaded spacer implantation in two-stage of THA in adults.…”
Section: Introductionmentioning
confidence: 99%